Challenging the prison-industrial complex : activism, arts, and educational alternatives - Hartnett, Stephen J. (University of Illinois Press, 2011)
Boldly and eloquently contributing to the argument against the prison system in the United States, these provocative essays offer an ideological and practical framework for empowering prisoners instead of incarcerating them. Experts and activists who have worked within and against the prison system join forces here to call attention to the debilitating effects of a punishment-driven society and offer clear-eyed alternatives, emphasizing working directly with prisoners and their communities.